Relações de saber-poder no pronunciamento de posse da presidente Dilma Rousseff - Silva, Renato Bernardo da (2013)
This dissertation aims at approaching the relation wisdom-power in Dilma Rousseff s Take-Office Speech in National Congress in January, 1st, 2011. As theoretical support it was taken Foucault s pieces (As palavras e as coisas, 1966; Arqueologia do saber, 1969; A ordem do discurso, 1970; and Microfísica do Poder, 1979). Analysis has emerged considering four themes taken as focus for examining such speech. Reasons for choices are justified considering their emphasis and relevance in life conception and intercourse. Education, the first one, profitable space to engaje in a controversy, a kind of control in Brazilian students, estimulating their insertion in a professional education. State Healthy, the second one, strategically approached through Body Discipline, aiming at reaching individual movement (action) and also by biopower, responsible by a stratagem of equilibrium and preservation of population. Both strategies work to produce behaviors and regulate life. The notion of taboo, the third theme, was thought from the use of the vocative brasileiros and brasileiras , working as a planned interdiction, in order to escape from future retaliations from government alliances. Media Class Growing, the last theme, is founded in the premise of alienated consume. By these themes, there is a crossing from the relation wisdom-power which emerges from Presidential Speech, working as social training tactics. Thus, Brazilian population becomes sick of an efficient educational system; a hospital system which makes sure life cure and preservation; a patterned taboo circulation and an illusion of economic ascension. In this context, a wisdom-power subject inscribes presidential take-office speech as a common individuality, subordinated and easy to be captured by wisdom-power nets.